Assessment of zinc in ​seminal stains and its application in forensic practice - Pavesi, Adriana (Universidad Autónoma de Tamaulipas, 2010)
The study of semen in legal medicine is a frequent fact that is why it takes importance in problems related to Criminal Law. Zinc (ZN) is found in prosthetic fluid in high concentration. The determination of Zinc in stains is proof that it can be utilized as the indicator of a seminal presence even in the absence of sperm. The objective of this work is to evaluate the levels of Zinc in seminal stains and its aplication in forensic practice. For this study 33 stains where analyzed, placing 0.2ml of seminal plasma over a dry canvas. Cuts where made on 0.7854 cm2 areas of stained cloth and 33 areas of the non stained cloths. There was also the mineralization of the matter to a final volume of 10ml determining Zinc by spectrophotometry of atomic absorption. All the material used was decontaminated with nitric acid to the 10%. The Zinc concentration was calculated by cm2 (square centimeters) for both groups of samples, the average for the stained clots remained a 23.47 ug/cm2 with a slight standard deviation of 0.09 and in the non stained cloths the average was 3.00 ug/cm2 with a standard deviation of 0.10. The student test was applied to compare the averages between both groups and the diferences where statistically big (P=0.006). Zinc determinations in seminal stains can be applied in sexually related crimes portrayed by azoospermic or oligozoospermic objects. Their cuantification in suspect stains can be considered for the exclusion of seminal plasma.